Effects of Exposure Conditions on Antioxidant Depletion, Tensile Strength, and Creep Modulus of Corrugated HDPE Pipes Made With or Without Recycled Resins - Nguyen, Khanh Q.; Cousin, Patrice; Mohamed, Khaled; Robert, Mathieu; Benmokrane, Brahim (Journal of polymers and the environment, 2022)
The service lifetime of corrugated high-density polyethylene (HDPE) pipes used in transportation infrastructure applications has been the subject of several studies over the years. How factors specific to North American climate conditions—such as freeze/thaw cycles, deicing salts, and abrasion—affect pipe service life have not been addressed. In this study, laboratory accelerated-aging tests were conducted to examine the thermo-oxidative degradation as well as tensile strength and creep modulus of HDPE pipes made with or without recycled resins. Specimens were immersed in saline solution (NaCl), acidic solution (H 2 SO 4 ), alkaline solution (NaOH) at 60 °C, or in water and exposed to freeze/thaw cycles ranging from − 40 to + 40 °C. Measuring the oxidative induction time (OIT) at various time intervals quantified the amounts of antioxidants present in the pipes, revealing that the rate of antioxidant depletion depended on the surrounding environment. The depletion rate was faster in the saline solution and slower in the freeze/thaw cycles. For specimens exposed to freeze/thaw cycles, the depletion was 1.12 to 1.91 lower than in the acidic solution, 1.25 to 2.64 times lower than in the alkaline solution, and 1.43 to 3.25 times lower than in saline solution. Nevertheless, the HDPE pipes all met the OIT requirements of a minimum of 20 min. Furthermore, the one-way analysis of variance (ANOVA) and Tukey’s HSD test indicate that the tensile strength and creep modulus values of the recycled and virgin HDPE pipes were unchanged before and after immersion in the different solutions.